Acute and Sub-acute Hypoglycaemic Evaluation of Cassia nodosa Leaves in Normal and Streptozotocin Induced Diabetic Rats - Kumavat, Urmila C. (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
In the present work, one novel ornamental plant Cassia nodosa Buch.-Ham. ex Roxb. has been investigated for antidiabetic potential. It aimed to check the hypoglycaemic effect of C. nodosa leaves on normal and streptozotocin-induced diabetic rats by acute and sub-acute studies. The qualitative and quantitative phytochemistry of the leaf drug was carried out by standard procedures. In preliminary phytochemistry antidiabetic compounds such as alkaloids, glycosides, steroids, flavonoids and saponins were detected. Quantitative phytochemistry revealed the presence of significant amounts of saponins (9.52%) and alkaloids (4.08%). Prior to the hypoglycaemic study, acute oral toxicity testing of the drug was performed. Later the effects of single and multiple doses of test drug were studied using various parameters. Dried powdered leaf material was used as an oral drug. Diabetes was induced in rats by a single intraperitoneal injection of streptozotocin. Single and multiple doses of test drug (0.5 g/kg body weight/day) were given to normal and diabetic rats. The parameters studied were blood glucose, serum cholesterol, serum triglycerides and serum proteins. The results of the test drug were compared with standard hypoglycaemic drug-glibenclamide (0.01 g/kg/day). It was done by the ‘Student’s ‘t’ test’ and the one-way ANOVA test. Unlike acute, sub-acute treatment of test drug showed a highly significant reduction (40.29%) in blood glucose levels of diabetic rats in 10 days. This effect was considerably good in comparison with standard drug (63.51%). The test drug and standard drug exhibited an insignificant change in the abnormal levels of serum metabolites of diabetic rats. Preclinically C. nodosa was proved to be an effective hypoglycaemic agent. Further studies are necessary to elucidate details of active phytochemicals and their mechanism of hypoglycaemic action.